How Banks in Bosnia and Herzegovina Use Social Networks? - Dražena Gašpar; Mirela Mabić; Damir Lucović (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Rovinj, Croatia, 8-9 September 2016, 2016)
The paper presents results of research related to the presence and activities of banks in Bosnia and Herzegovina on social networks. The results of research show that banks in Bosnia and Herzegovina mostly use Facebook, mainly as a marketing tool. Although customer engagement is essential in the banking industry, banks in Bosnia and Herzegovina are still not very successful in using social networks as a real communication tool. Namely, social networks are a very powerful channel through which banks could reach out to their customers in order to find what products their customers want, what decisions they can make to improve relations with customers and what they may be doing that annoys their customers. But, it seems that banks do not understand that they need to be willing to implement some of customers suggestions posted on social networks, otherwise customers will not come back, will not become fans or loyal friends of the tribe. The paper shows that there is a lot of room for improvement in the use of social networks in banks in Bosnia and Herzegovina and provides some important guidelines and suggestions on how banks could use social networks to enhance relationships with customers and develop mutual trust.
Keywords: O39; 330; social network; banks; social networks research; Facebook; Twitter